Spatial characteristics and ecological wisdom of Amdo Tibetan traditional dwellings in western Sichuan - Likai Lin; Yan Gui (Journal of Asian Architecture and Building Engineering)
Amdo Tibetans are an important part of the three major Tibetan areas in western Sichuan. Their production and life style rooted in the Ruoergai grassland pastoral area is significantly different from that of Kangba Tibetans and Jiarong Tibetans, which are widely distributed in the valley areas. However, due to the relatively small population size and distribution range, there is still a lack of research on the space of multi-Tibetan settlements in western Sichuan, which makes the unique spatial characteristics of grassland dwellings and their generation logic unclear. Based on a large number of literature studies and field investigations, this paper systematically analyzes its location pattern, spatial layout and material application from the perspective of ecological wisdom through spatial analysis, comparative analysis and other methods. The results show that there are obvious differences in spatial form between the Tibetan dwellings in Anduo grassland in western Sichuan and the Tibetan settlements in Kangba and Jiarong. The scattered siting model is used to cope with the impact of bad climate and the characteristics of widely dispersed production factors. The diversified, specialized and open yard space layout is adapted to the production mode of pastoral areas. Local materials such as manure are used to build settlement space according to local conditions. This study reveals the spatial characteristics and environmental adaptation wisdom of multi-Tibetan grassland dwellings in western Sichuan, complements and improves the Tibetan research system and content in western Sichuan, and provides theoretical guidance for the healthy and sustainable development of multi-Tibetan settlements in western Sichuan.